Active Displacement of a Unique Diatom–Ciliate Symbiotic Association - Yonara Garcia; Felipe M. Neves; Flavio R. Rusch; Leandro T. De La Cruz; Marina E. Wosniack; J. Rudi Strickler; Marcos G. E. da Luz; Rubens M. Lopes (Fluids)
Adaptive movement in response to individual interactions represents a fundamental evolutionary solution found by both unicellular organisms and metazoans to avoid predators, search for resources or conspecifics for mating, and engage in other collaborative endeavors. Displacement processes are known to affect interspecific relationships, especially when linked to foraging strategies. Various displacement phenomena occur in marine plankton, ranging from the large-scale diel vertical migration of zooplankton to microscale interactions around microalgal cells. Among these symbiotic interactions, collaboration between the centric diatom Chaetoceros coarctatus and the peritrich ciliate Vorticella oceanica is widely known and has been recorded in several studies. Here, using 2D and 3D tracking records, we describe the movement patterns of the non-motile, chain-forming diatoms (C. coarctatus) carried by epibiotic ciliates (V. oceanica). The reported data on the Chaetoceros–Vorticella association illustrated the consortium’s ability to generate distinct motility patterns. We established that the currents generated by the attached ciliates, along with the variability in the contraction and relaxation of ciliate stalks in response to food concentration, resulted in three types of trajectories for the consortium. The characteristics of these distinct paths were determined using robust statistical methods, indicating that the different displacement behaviors allowed the consortium to adequately explore distributed resources and remain within the food-rich layers provided in the experimental containers. A simple mechanical–stochastic model was successfully applied to simulate the observed displacement patterns, further supporting the proposed mechanisms of collective response to the environment.